Attachment Style of Volunteer Counselors in Telephone Emergency Services Predicts Counseling Process - Dinger, Ulrike; Jennissen, Simone; Rek, Isabelle (Frontiers in Psychology, 2019)
Telephone emergency services (TES) play an important role in counseling and suicide prevention. The current study examines a potential change of volunteer counselors’ attachment characteristics during TES training and investigates the predictive influence of counselor attachment for their competence and working alliance with callers. We recruited 261 volunteers enrolled in training for paraprofessional counseling in the German Telephone Emergency System (Telefonseelsorge). Participants were assessed three times during their training (mean training duration 13.3 months) and responded to questionnaires on adult attachment (Experience in Close Relationships-Revised) and their counseling competence (adapted Development of Psychotherapists Common Core Questionnaire). In addition, they indicated the quality of the working alliance (adapted Working Alliance Inventory – Short, Revised) with their client callers upon training completion. Results showed that attachment anxiety, but not attachment avoidance, significantly decreased during training. Lower attachment avoidance predicted better working alliances with callers as well as better general skillfulness. Implications for training of volunteer telephone counselors are discussed.